(3GdGSJbUGA hGdEHQGe aj YdGL GdLQGMGJ hGdChQGes - (3eMeO Hf Ydj Hf aQL GdagQj GdTaQI GdbQHdjGfj,J (B722 (3g` s
(3ChdgG (B:s
(3aEfg deG QCjJ UfGYI GdLQGMGJ ef CZeV CUfGa GdWH GSJNQJ Gddg JYGdi ai JCdja cJGH jMUQ YdGLgG hjVHW eLehYgG s
(3BNQgG (B:s
(3hgPG BNQ eG hLO ef gPG GdJCdja GdYLjH , eY eG ajg ef GdJUMja hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B165 - (3U(B185s
(3GfXQ eLdI eYgO GdeNWhWGJ(B309/5s
(3GfXQg eY JPcQI Chdi GdCdHGH (B"369(3, (B370" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1363 (3O(B) s
Keywords: (3GdWHs